What Drives Muslims to Endow? Examining Attitude, Subjective Norms, and Religiosity through the Mediating Role of Intention - Husain, Alfi Zikri; Siregar, Rosnani; Hasibuan, Abdul Nasser (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: This study examines the behavioral determinants of waqf participation within the framework of the Theory of Planned Behavior by incorporating religiosity as an extended variable and intention as a mediating factor. The research aims to analyze the influence of attitude, subjective norms, and religiosity on the intention and decision to perform waqf, as well as to investigate the mediating role of intention in a pesantren-based waqf institution.Methods: A quantitative causal-explanatory design was employed using data collected from 100 waqif at LAZISWA Pondok Pesantren Mawaridussalam, North Sumatra. Data were analyzed using Structural Equation Modeling–Partial Least Squares. Results: The results indicate that attitude and religiosity have significant positive effects on both waqf intention and waqf decision, while subjective norms significantly influence waqf decision but do not affect intention. Intention is proven to significantly influence waqf decision and partially mediates the relationship between attitude and religiosity on waqf decision, but does not mediate the effect of subjective norms. Religiosity emerges as the most dominant determinant, highlighting the central role of spiritual motivation in Islamic philanthropic behavior.Conclusion and suggestion: These findings suggest that strengthening internal factors, particularly religiosity and positive attitudes, is more effective than relying on social pressure in enhancing waqf participation. This study contributes to the development of an extended behavioral model of waqf and provides strategic implications for waqf institutions to design more effective engagement approaches based on spiritual and psychological factors.